Neoadjuvant Therapy for Pancreatic Ductal Adenocarcinoma: Where Do We Go? - Wang, Chenqi; Tan, Guang; Zhang, Jie; Fan, Bin; Chen, Yunlong; Chen, Dan; Yang, Lili; Chen, Xiang; Duan, Qingzhu; Maimaiti, Feiliyan; Du, Jian; Lin, Zhikun; et al. (Frontiers in Oncology, 2022)
The incidence of pancreatic ductal adenocarcinoma (PDAC) has been on the rise in recent years; however, its clinical diagnosis and treatment are challenging. Although radical surgical resection remains the only chance for long-term patient survival, the proportion of initial resectability is no more than 20%. Thus, neoadjuvant or adjuvant chemotherapy plays an important role in the comprehensive treatment. The novel concept of neoadjuvant therapy (NAT) in PDAC aims to transform the proportion of inoperable PDACs into operable cases to improve overall survival. At present, the results of many clinical trials, including prospective and retrospective studies with large cases, have validated its position in PDAC therapy, including prolongation of overall survival, increased R0 resection, and a higher proportion of negative lymph nodes. However, there are still some debates regarding the role of NAT in PDAC treatment, such as indications of NAT application in different stages of PDAC, selection of regimens, duration of treatment, and assessment of effect. This review aims to summarize the current progress and controversies of NAT in PDAC. Simultaneously, we updated other evidence of high-quality radiotherapy and targeted therapy with our own opinions to discuss key findings reported in recent years.